Reconsidering Authorship in the Ciceronian Corpus through Computational Authorship Attribution - Raija Vainio; Reima Välimäki; Anni Hella; Marjo Kaartinen; Teemu Immonen; Aleksi Vesanto; Filip Ginter (Ciceroniana On Line, 2019)
In recent years, methods of computational authorship attribution have offered promising results for the reattribution of classical texts. We use and further develop these methods to verify the authorship of several texts belonging or related to the Ciceronian corpus: Rhetorica ad C. Herennium, De inventione, De optimo genere oratorum, and Commentariolum petitionis. We use two classifiers, Support Vector Machine and Convolutional Neural Network, of which the latter is more accurate except in regard to certain aspects of vocabulary. The most important of our results is that Commentariolum petitionis seems to be authored by Marcus Cicero, not by his brother Quintus.